Modern Problems of Stochastic Analysis and Statistics: Selected Contributions In Honor of Valentin Konakov - Panov, Vladimir (Springer Proceedings in Mathematics & Statistics, 2017)
0. Preface -- List of contributors -- 1. Youri Davydov, Valentin Konakov, Roberto Garra and Enzo Orsingher: Random motions -- 2. Aurélien Alfonsi, Masafumi Hayashi, Arturo Kohatsu-Higa, Gennaro Cibelli and Sergio Polidoro: Parametrix and heat kernel estimates -- 3. Ion Grama and Emile Le Page: Local limit theorems -- 4. Denis Belomestny, Stefan Häfner, Mikhail Urusov, Alexander Gushchin and Esko Valkeila: Approximation of stochastic processes -- 5. Alexandre Richard, Denis Talay, Yuliya Mishura and Kostiantyn Ralchenko: Fractional Brownian motion -- 6. Alexander Lykov, Vadim Malyshev, Bernard Derrida and Zhan Shi: Particle systems -- 7. Pierre Bellec, Alexandre Tsybakov and Enno Mammen: Statistics -- 8. Ekaterina Bulinskaya: Acturial science -- 9. Dan Han, Stanislav Molchanov, Joseph Whitmeyer: Population dynamics -- 10. Alexander Veretennikov: Ergodic Markov processes